Comprehensive monitoring of a special mixture of prominent endocrine disrupting chemicals in human urine using a carefully adjusted hydrolysis of conjugates - Denghel, Heike; Göen, Thomas (Analytical and Bioanalytical Chemistry, 2022)
Many xenobiotics were identified as possible endocrine disruptors during the last decades. Structural analogy of these substances to natural hormones may lead to agonists or antagonists of hormone receptors. For a comprehensive human biomonitoring of such substances, we developed a simple, reliable, and highly sensitive method for the simultaneous monitoring of the parameters bisphenol A, triclosan, methylparaben, ethylparaben, propylparaben, butylparaben, benzophenone-1, benzophenone-3, 3,5,6-trichloropyridin-2-ol, p-nitrophenol, genistein, and daidzein in urine. Thereby, optimization of the enzymatic hydrolysis and the use of β-glucuronidase from E. coli K12 as well as sulfatase from Aerobacter aerogenes ensures the acquisition of intact analytes without cleavage of ester bonds among parabens. Validation of the method revealed limits of detection between 0.02 and 0.25 µg/L as well as limits of quantification between 0.08 and 0.83 µg/L. Thereby, the use of analyte-free surrogate matrix for calibration and control material influenced the sensitivity of the procedure positively. Furthermore, excellent precision in and between series was observed. Good absolute and relative recoveries additionally proved the robustness of the multimethod. Thus, the procedure can be applied for exploring the exposome to these prominent endocrine disruptors in the general population. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-12-02
Keywords: Conjugates; Endocrine disrupting chemicals; Enzymatic hydrolysis; GC-MS/MS; Human biomonitoring; Phenols